Contribution of Accredited Social Health Activist (ASHA) under the Community Health Model of National Health Mission, India - Khanna, Rajat; Prakash, Dr. Nirupama; Sharma, Alka (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Under the Community Health programme of National Health Mission (NHM), one of the key component is providing a trained female Community Health Worker (CHW) named as Accredited Social Health Activist (ASHA) in every village of the country to serve the most marginalized and vulnerable rural population. Methodology: Quantitative data collection method was used in this research. The data was collected from a purposive random sample of 309 ASHA which were interviewed through a structured questionnaires on their knowledge and practices on child health. Results: 88% ASHAs were found with Correct Knowledge of Complementary Feeding, 92% ASHAs had Correct Knowledge of ORS preparation, 85% ASHAs had Knowledge of Timely Initiation at correct age of Pediatric IFA syrup, 88% ASHAs had Knowledge on correct Pediatric IFA quantity, 94% ASHAs were found with Knowledge on correct Pediatric IFA frequency, 61% ASHAs had Correct Knowledge on danger sign detection, and 36% ASHAs were found with Correct Knowledge on SNCU discharge instructions. 84% ASHAs were found to be providing regular and structured Home visits to mothers on Child Health, 88% ASHAs were providing counselling on complementary feeding, 80% were ASHAs providing counselling on Exclusive Breastfeeding feeding, 92% ASHAs were providing counselling on ORS use during Diarhoea episodes, 85% ASHAs were providing counselling on Pediatric IFA supplementation, 61% ASHAs were providing counselling on danger Signs detection, However, only 10% ASHAs had referred sick infants to health facilities.